Der Stoff der Räume Textile Raumkonzepte im französischen Interieur des 18. Jahrhunderts - Reineke, Anika (Textile Studies, 2020)
Textiles were central material and medium of the European interior in early modern Western and Central Europe. Anika Reineke opens up new perspectives on the aesthetics of the Rococo period, with a particular focus on spatial concepts, illusionism, and craftsmanship. Using tapestries, silk wall coverings, and screens as examples, this transmedial study offers up-to-date perspectives on the plural authorship of craftsmen and artists, the visual effects of room furnishings, and the ambivalent relationship between guilds, manufactories, and academies in the 18th century.